Determination of arm fat area and arm muscle area norms in children 6-12 years of age in Bursa - Günay, Ünsal; Sapan, Nihat; Salih, Celal; Doğruyol, Hasan (The Turkish Journal of Pediatrics, 1990)
Since arm fat area and arm muscle area measurements are said to assess the calorie and protein reserves in the body more accurately than triceps skinfold thickness measurements, we decided to use this system on 1497 girls and 1651 boys who were pupils in elementary schools in Bursa. From the data obtained, percentile norms for the children aged between 6-12 were calculated and percentile curves were drawn. The data that we collected can be used in future nutritional surveys.
Keywords: malnutrition; arm fat area; arm muscle area